2020
DOI: 10.1016/j.jalz.2019.08.194
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of self‐reported hearing loss and subjective cognitive function decline in women

Abstract: Introduction We investigated the relation between self‐reported hearing loss and risk of subjective cognitive function (SCF) decline among women. Methods We conducted a longitudinal study of 20,193 women in the Nurses’ Health Study aged ≥66 years who reported their hearing status and had no subjective cognitive concerns in 2012. SCF scores were assessed by a 7‐item questionnaire in 2012 and 2014. SCF decline was defined as a new report of at least one cognitive concern during follow‐up. Results Self‐reported h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 85 publications
1
21
0
1
Order By: Relevance
“…This may be due to their brain processing sound abnormally. Most large population-based longitudinal studies rely on self-reported hearing problems to establish the association of hearing impairment with dementia [ 7 , 8 ]. A recent systematic review of the links between hearing impairment and dementia found that only a few articles in the field measured hearing through the PTA, while participant self-reporting was often used [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to their brain processing sound abnormally. Most large population-based longitudinal studies rely on self-reported hearing problems to establish the association of hearing impairment with dementia [ 7 , 8 ]. A recent systematic review of the links between hearing impairment and dementia found that only a few articles in the field measured hearing through the PTA, while participant self-reporting was often used [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has already been known that ARHI and AD differ in prevalence in terms of sex-ARHI is more common and severe in men, while the incidence of AD is greater in women (21-23)-but whether sex predisposes older adults with hearing loss to greater risk of cognitive impairment is a subject of controversy. There is a lack of consensus regarding sex-differing risk in this area, when such data were disaggregated by biological sex (14,(24)(25)(26). Although social and cultural behavior has been one explanation for these previous findings, the systematic consideration of one's psychosocial sex-the state of being an older man or woman under the influence of culture and society-remains rare.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates from the National Health and Nutrition Examination Survey suggest that 48 million US adults suffer from hearing loss. 1 Hearing loss may be associated with impaired communication, decreased quality of life, depression, [2][3][4] and cognitive decline, 5,6 thus understanding how modifiable factors may influence risk could provide new insights into possibilities for prevention or delay of acquired hearing loss.…”
Section: Introductionmentioning
confidence: 99%